Night air conditioning of buildings by external air ventilation - Bravo-Hidalgo, Debrayan (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Buildings contain the environment in which almost all human activities take place, and therefore, nowadays, they represent a great sink of energy. Establishing thermal comfort conditions within these buildings is responsible for a large portion of their energy demand. This paper aims at providing a theoretical framework of the performance and the trends in research and implementation of night air conditioning by outside air ventilation. The bibliographic search was conducted in the academic directory Scopus, and the information extracted was processed in the VOSviewer software, through which text mining, map of terms and networks of investigative action were carried out. The literature showed that direct ventilation has a more significant cooling potential in regions characterized by a high difference between day and night air temperatures. The effectiveness of night cooling and the reliable prediction of thermal behavior are strongly related to the model adopted for the convection algorithm. A reliable prediction of heat transfer by convection requires an approach based on computational simulations of fluid dynamics, which are much more demanding in terms of computational power, compared to simulations of the variation of energy flows as a function of time. Most studies showed that the position of the thermal mass is not significant, while the amount of ventilation air is of great importance. In particular, the energy demand for cooling a building decreases sharply if the air flow rates increase.